Spatial variation of nitrogen cycling in a subtropical stratified impoundment in southwest China, elucidated by nitrous oxide isotopomer and nitrate isotopes. Issue 2 (3rd April 2018) - Yue, Fu-Jun; Li, Si-Liang; Liu, Cong-Qiang; Mostofa, Khan M.G.; Yoshida, Naohiro; Toyoda, Sakae; Wang, Shi-Lu; Hattori, Shohei; Liu, Xiao-Long
ABSTRACT: Estimates of biogeochemical processes and the proportion of N2 O production in the aquatic system of impoundments are important to quantify nitrogen cycling, particularly during stratification periods. In this study, we used the dual isotopes of nitrate (NO3 − ) and nitrous oxide (N2 O) to estimate the nitrogen dynamics and contributions to N2 O production and reduction at varying zones in Lake Baihua, located in southwest China. The lake was strongly stratified during the sampling period, with the oxic zone from the surface to 12  m and the anoxic zone from 12 to 21  m. The assimilation shifted δ 15 N and δ 18 O of NO3 − significantly in the epilimnion (0−4  m), and denitrification contributed to the shift in the low dissolved oxygen zone of the hypolimnion. The semiquantitative analysis showed that nitrification accounted for >67% of the N2 O production between 0 and 4  m while higher nitrification contributions were also found between 6 and 12  m. The contribution of denitrification between 15 and 21  m was >43%. The mechanism responsible for the vertical variations should be considered in the estimation of nitrogen cycling and N2 O production in subtropical stratified impoundments.